2014
DOI: 10.1515/jcim-2014-0051
|View full text |Cite
|
Sign up to set email alerts
|

An emphasis on molecular mechanisms of anti-inflammatory effects and glucocorticoid resistance

Abstract: Glucocorticoids (GC) are universally accepted agents for the treatment of anti-inflammatory and immunosuppressive disorders. They are used in the treatment of rheumatic diseases and various inflammatory diseases such as allergy, asthma and sepsis. They bind with GC receptor (GR) and form GC-GR complex with the receptor and exert their actions. On activation the GC-GR complex up-regulates the expression of nucleus anti-inflammatory proteins called as transactivation and down-regulates the expression of cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…This phenomenon may be explained by (i) increased Rg1-mediated GR transcriptional repression or (ii) reduced Rg1-mediated GR deacetylation via HDAC2 up-regulation. A reduction in GR levels is one of the mechanisms that contributes to GC resistance2. We also found that Rg1 up-regulated GR expression, which might be explained by the effects of deacetylation on ubiquitin and protein binding, resulting in the loss of selective GR degradation1244.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This phenomenon may be explained by (i) increased Rg1-mediated GR transcriptional repression or (ii) reduced Rg1-mediated GR deacetylation via HDAC2 up-regulation. A reduction in GR levels is one of the mechanisms that contributes to GC resistance2. We also found that Rg1 up-regulated GR expression, which might be explained by the effects of deacetylation on ubiquitin and protein binding, resulting in the loss of selective GR degradation1244.…”
Section: Discussionmentioning
confidence: 59%
“…Therapeutic strategies to restore GR levels are urgently needed to overcome the challenge of GC resistance240. In this study, we demonstrated that the ginsenoside Rg1 effectively reversed UVB-induced Dex insensitivity by up-regulating the GR and that these effects were partially mediated by the Nrf2/HDAC2 pathway.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Synthetic glucocorticoids (GCs) are the most effective anti-inflammatory therapy for disease including rheumatic diseases, allergy, asthma, and sepsis. However, GC resistance limits the therapeutic response of GCs in certain chronic inflammatory diseases including severe asthma, IPF, and cancer [ 104 ]. GC resistance has been attributed to cellular microenvironment changes, that is, alterations in the ECM, as a consequence of chronic inflammation [ 105 ].…”
Section: Inflammatory Actions Of Coagulant Proteases Are Glucocormentioning
confidence: 99%
“…Because of their potent pro-apoptotic and anti-inflammatory properties and capability to reduce nausea and acute toxicity in normal tissues, GCs have been widely used as components of chemotherapy regimens for treatment of leukemias, lymphomas, and myelomas ( Kim et al, 2004 ). Although GPx3 was not identified in profiling of primary GR target genes by chromatin immunoprecipitation (ChIP) ( Polman et al, 2012 ; Wang et al, 2004 ), we decided to further investigate the role of GCs in the regulation of GPx3 expression because the activated GC-GR complex up-regulates the expression of anti-inflammatory proteins in the nucleus ( Ingawale et al, 2015 ), and because GPx3 is a strong tumor suppressor in many types of cancers. Our findings demonstrate that GR can increase GPx3 expression in lung cancer, suggesting that the GPx3 promoter might be a direct target of GC-mediated signaling in tumor cells.…”
Section: Introductionmentioning
confidence: 99%